Opportunities for convergence and regional cooperation - Rosales, Osvaldo (UN ECLAC SantiagoCL, 2010)
Examines opportunites for regional cooperation in eight areas : infrastructure, aid for trade, strengthening the social component of integration, the reduction of asymmetries, innovation and competitiveness, joint pursuit of closer ties with Asia-Pacific, the reform of the international financial system, and climate change.